2018
DOI: 10.3389/fnagi.2018.00342
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Brain Activity Changes After Mnemonic Strategy Training in Amnestic Mild Cognitive Impairment: Evidence From a Randomized Controlled Trial

Abstract: Background: Mnemonic strategy training (MST) has been shown to improve cognitive performance in amnestic mild cognitive impairment (a-MCI), however, several questions remain unresolved. The goal of the present study was to replicate earlier pilot study findings using a randomized controlled design and to evaluate transfer effects and changes in brain activation.Methods: Thirty patients with a-MCI were randomized into MST or education program. At baseline, participants completed clinical and neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 118 publications
(169 reference statements)
8
48
0
Order By: Relevance
“…These patterns may reflect a difference in approach taken by APOE4 carriers and non-carriers to complete the task. For example, mnemonic strategy training appears to improve performance on face-name associative memory tasks and further correlate with increased frontoparietal activity in older adults with amnesic mild cognitive impairment [89,90]. We did not assess strategy use in the present study and were therefore unable to test this possibility directly.…”
Section: Apoe4-based Differences In Brain-behavior Correlationsmentioning
confidence: 85%
“…These patterns may reflect a difference in approach taken by APOE4 carriers and non-carriers to complete the task. For example, mnemonic strategy training appears to improve performance on face-name associative memory tasks and further correlate with increased frontoparietal activity in older adults with amnesic mild cognitive impairment [89,90]. We did not assess strategy use in the present study and were therefore unable to test this possibility directly.…”
Section: Apoe4-based Differences In Brain-behavior Correlationsmentioning
confidence: 85%
“…Therefore, the aim of the current study was to investigate the behavior effects and the neural correlates of MST in patients with chronic stroke lesions in the left hemisphere using fMRI before and after the training. We replicated similar procedures from previous studies that showed effective MST during the associative encoding of face-name pairs in MCI patients [1113] that was previously adapted for Brazilian population [12, 15].…”
Section: Introductionmentioning
confidence: 76%
“…Difficulties in recalling people's names can produce important impact on social interactions and communication. Previous studies in patients with amnestic mild cognitive impairment (aMCI), a neurodegenerative condition, using face-name mnemonic strategy training (MST), showed significant behavior improvement associated with recruitment of widespread cerebral networks including the frontoparietal, inferior parietal cortex, temporal and fusiform gyri, angular gyrus, posterior cingulate cortex, and precuneus using functional magnetic resonance imaging (fMRI) [11, 12]. MCI training gains were evident on similar measures in the same trained cognitive domain (“near-transfer effect”) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns may reflect a difference in approach taken by -APOE4 and +APOE4 individuals to complete the task. For example, mnemonic strategy training appears to improve performance on face-name associative memory tasks and further correlate with increased frontoparietal activity in older adults with amnesic mild cognitive impairment (Simon et al, 2018(Simon et al, , 2019). However, because task instructions did not direct participants to use any particular approach or strategy, and based on the lack of behavioral differences, this seems unlikely to explain the observed findings.…”
Section: Apoe4-based Differences In Brain-behavior Correlationsmentioning
confidence: 99%